Helicobacter mustelae and Helicobacter pylori bind to common lipid receptors in vitro. - Gold, B D (1993)
Helicobacter pylori is a recently recognized human pathogen causing chronic-active gastritis in association with duodenal ulcers and gastric cancer. Helicobacter mustelae is a closely related bacterium with similar biochemical and morphologic characteristics. H. mustelae infection of antral and fundic mucosa in adult ferrets causes chronic gastritis. An essential virulence property of both Helicobacter species is bacterial adhesion to mucosal surfaces. The aim of this study was to determine whether H. mustelae binds to the same lipids shown previously to be receptors for H. pylori adhesion in vitro. By using thin-layer chromatography overlay and a receptor-based enzyme-linked immunosorbent assay, H. mustelae was found to bind the same receptor lipids as H. pylori, namely, phosphatidylethanolamine and gangliotetraosylceramide. In addition, both H. pylori and H. mustelae bound to a deacylplasmalogen phosphatidylethanolamine. In contrast to H. pylori, H. mustelae binding to receptors was unaffected by motility or viability. Murine monoclonal and bovine polyclonal antibodies against exoenzyme S, and exoenzyme S itself (from Pseudomonas aeruginosa), inhibited binding of H. mustelae to phosphatidylethanolamine and gangliotetraosylceramide. These findings show that H. mustelae binds in vitro to the same lipid receptors as H. pylori and suggest that the adhesion of H. mustelae to such species is mediated by preformed, surface-exposed adhesins which include an exoenzyme S-like protein.